2016
DOI: 10.2136/sssaj2015.09.0348
|View full text |Cite
|
Sign up to set email alerts
|

Surface Application of Lime–Silicate–Phosphogypsum Mixtures for Improving Tropical Soil Properties and Irrigated Common Bean Yield

Abstract: Core Ideas Soil acidity limits crop production in tropical regions. Soil amendments mixture can be a strategy to alleviate subsoil acidity. Subsoil profile acidity reduces common bean grain yield. The movement of surface‐applied lime to subsurface soil layers is slow, and, consequently, liming requires a long period of time to become effective. Thus, it is important to develop strategies to increase the efficiency of acidity amendments practices in order to improve the chemical properties of tropical acid soil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 45 publications
2
9
0
1
Order By: Relevance
“…The pH (CaCl 2 ) results in this study showed an opposite trend to pH (H 2 O), especially for unlimed MO soil as its pH (CaCl 2 ) increased slightly with PG. This confirmed what was reported recently about the increase of soil pH at depths of 0 to 5 cm by Crusciol et al [ 27 ], after the surface application of phosphogypsum. Further, this result corroborates early reports by Toma et al [ 4 ], who found that gypsum application decreased pH (H 2 O) while pH (CaCl 2 ) did not.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The pH (CaCl 2 ) results in this study showed an opposite trend to pH (H 2 O), especially for unlimed MO soil as its pH (CaCl 2 ) increased slightly with PG. This confirmed what was reported recently about the increase of soil pH at depths of 0 to 5 cm by Crusciol et al [ 27 ], after the surface application of phosphogypsum. Further, this result corroborates early reports by Toma et al [ 4 ], who found that gypsum application decreased pH (H 2 O) while pH (CaCl 2 ) did not.…”
Section: Discussionsupporting
confidence: 93%
“…Phosphogypsum is used in agriculture all over the world, for example in Brazil, Spain, Australia, India, Pakistan, USA and Egypt [ 18 , 19 , 20 ], either as soil amendment under the category “Calcium sulphate” or as fertilizer [ 21 ]. Several benefits of PG application in agriculture have been reported worldwide for saline/sodic soils [ 22 , 23 , 24 ] or acidic soils [ 25 , 26 , 27 , 28 ]. However, research on PG application on acid soils has mostly focused on its effects in alleviating the toxic effects of high Al bioavailability or used in providing calcium for crops [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In NT, Poaceae such as corn (Zea mays L.) (Caires et al 2011a) and wheat (Triticum aestivum L.) (Vicensi et al 2016) have shown increased yields after gypsum application. The Fabaceae crops, such as soybean (Costa and Crusciol 2016) and common bean (Crusciol et al 2016;…”
Section: Introductionmentioning
confidence: 99%
“…Agricultural or mineral gypsum (CaSO 4 .2H 2 O) is being widely used as source of nutrients such as calcium and sulfur and to adjust aluminum toxicity in the deeper soil layers (Caires et al, 2006;Nora and Amado, 2013), after correction of the pH in the surface layer by liming. Some studies have indicated that gypsum is an important complement to liming in the presence of high Al 3+ levels in the subsoil (Soratto and Crusciol, 2008;Caires et al, 2010;Crusciol et al, 2016). Thus, gypsum is considered a subsurface amendment for root growth, reducing toxic levels of aluminum and increasing calcium levels in the soil profile (Caires et al, 2002;Pauletti et al, 2014).…”
Section: Introductionmentioning
confidence: 99%